Higher incidence of steroid-induced ocular hypertension in keratoconus. Issue 1 (December 2016) - Kanellopoulos, Anastasios; Cruz, Emerson; Ang, Robert; Asimellis, George
Abstract Background To compare intraocular pressure (IOP) changes following topical dexamethasone administration for 1 month in keratoconic versus normal eyes. Methods This is a retrospective, single-center, non-randomized case series evaluation of 350 eyes. Two groups were formed: normal/control Group A (nA =73), eyes that underwent excimer laser photorefractive keratectomy; and keratoconic (KCN) Group B (nB =277), eyes that were subjected to partial laser photorefractive keratectomy combined with collagen cross-linking (The Athens Protocol). All eyes received the same post-operative regimen of topical dexamethasone 0.1 % for at least 1 month. Goldmann applanation tonometry IOP readings and central corneal thickness (CCT) measurements were monitored. Cases with induced ocular hypertension (OHT, defined as post-operative IOP higher than 21 mmHg), were identified and correlated to refractive procedure, gender, and corneal thickness. Results At 4 weeks postoperatively, OHT was noted on 27.4 % (20 /73 eyes) in Group A, and 43.7 % (121 /277 eyes) in KCN Group B, (p <0.01). Six months post-operatively (following 5-months of discontinuing topical dexamethasone treatment and commencing treatment of IOP-lowering medications), OHT rate was 1.8 % in Group A and 3.9 % in the KCN Group B. Conclusion This study demonstrates a potentially significant pre-disposition of keratoconic eyes to the development of steroid-induced OHT.